2019
DOI: 10.4149/bll_2019_128
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia among hospitalized internal medicine patients: A cross-sectional single-center pilot study according to EWGSOP2 criteria

Abstract: INTRODUCTION: Sarcopenia is associated with a higher risk of adverse outcomes among hospitalized patients with chronic diseases. Currently, an unmet need lies in its low diagnostic yield. We conducted a pilot study with the aim to screen hospitalized patients for sarcopenia using the EWGSOP2 criteria. PATIENTS AND METHODS: A cross-sectional study among hospitalized patients in internal medicine was carried out, inclusion criteria: age>55, ability to stand-up from a chair. Exclusion criteria: bed-bound, termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
1
4
1
1
Order By: Relevance
“…Associations of low calf circumference [32], malnutrition [2] and cognitive impairment [3] with sarcopenia are well known. A previous pilot study used the new criteria of EWGSOP2 to analyze parameters for association with sarcopenia and found, in contrast to our data, only low MAC to be positively associated with the disease, although causality cannot be established in a cross-sectional study [33]. However, the sample size of this study was small (n = 40), and the patients were younger (mean age of 70.0 years) compared to our cohort.…”
Section: Discussioncontrasting
confidence: 94%
“…Associations of low calf circumference [32], malnutrition [2] and cognitive impairment [3] with sarcopenia are well known. A previous pilot study used the new criteria of EWGSOP2 to analyze parameters for association with sarcopenia and found, in contrast to our data, only low MAC to be positively associated with the disease, although causality cannot be established in a cross-sectional study [33]. However, the sample size of this study was small (n = 40), and the patients were younger (mean age of 70.0 years) compared to our cohort.…”
Section: Discussioncontrasting
confidence: 94%
“…Male participants had higher likelihood of confirmed sarcopenia compared to females. Similar results have been reported previously [2,32]. Some studies mentioned that age-related decrease in sex hormones is a major contributor to loss of lean mass and increase in fat mass for both genders [33].…”
Section: Associated Parameters Of Confirmed Sarcopeniasupporting
confidence: 90%
“…Sarcopenia is a geriatric syndrome that could be caused by aging, body composition change and chronic diseases [1]. A high prevalence of sarcopenia can cause heavy healthcare expenditure and caregiver burden [2,3]. Many studies have indicated that older adults with sarcopenia were associated with increased falling rate, comorbidities, malnutrition, functional disabilities and mortality rate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“… 24 But the new diagnostic criteria provide a relatively simple and applicable tool for screening among patients. 25 Only few studies in geriatric psychiatric institutions considering older adults suffering from dementia, depression, or delirium have been conducted yet. A recent review analysis included 11 studies with persons suffering from dementia or cognitive impairment and calculated a prevalence rate of sarcopenia of 26.4% (95% confidence interval: 13.6–44.8%) in individuals with dementia compared with 8.3% in their controls.…”
Section: Introductionmentioning
confidence: 99%